BEHIND THE TRASH: A QUALITATIVE RESEARCH ON HOW TRASH PICKERS IN CIRENDEU AREA CONTRIBUTE TO RECYCLING - Kakinuma, Mana (UI Scholars Hub, 2019)
Trash is one of the most serious environmental issues. People strive to solve the problem with reducing the use of plastic and figuring out the method to recycle efficiently; however, the story of trash pickers is barely on the topic. The problems are the ignorance and underestimation of the society. People should consider the integrated solution for both the environment and those trash pickers. The ideal solution would be formalizing waste disposal system, officially hire trash pickers for their stable life, and let their children access to education for brighter future. This discussion will examine the importance of understanding the people behind the trash by investigating the trash pickers community in Cirendeu, Indonesia. Before doing the research, the author has visited the communities several times and had been given the impression of pity, poor and helplessness; however, since the waste management system in Indonesia is unclear, they must be playing a significant role. The author carried qualitative research including fieldwork and interview in Bahasa Indonesia, with supports from a local non-profit organization, XSProject, which has been communicating and supporting the trash pickers for a decade. The results from the research indicate that they contribute to recycle to a great extent. Their waste disposal method is quite systemized. They are also skillful, active and ambitious. There is a person who has the second job, skill to make aquarium for his children, own shops and teach sewing. All group leaders of trash pickers, called Lapak have a skill to build houses and carts for his men, anak-buah. Their skills of sorting the trash let XSProject reuse more than hundreds of kilograms of plastics including plastic packaging, grocery bags and rice sacs each year. Their contribution for Indonesian environment is underrated although it is huge.